2018
DOI: 10.1097/md.0000000000012246
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of magnetic resonance T1 mapping with dilated cardiomyopathy

Abstract: The diagnosis of dilated cardiomyopathy (DCM) remains a challenge in clinical radiology. This study aimed to investigate whether texture analysis (TA) parameters on magnetic resonance T1 mapping can be helpful for the diagnosis of DCM.A total of 50 DCM cases were retrospectively screened and 24 healthy controls were prospectively recruited between March 2015 and July 2017. T1 maps were acquired using the Modified Look-Locker Inversion Recovery (MOLLI) sequence at a 3.0 T MR scanner. The endocardium and epicard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Recent studies indicated that homogeneity, energy, and correlation were higher in patients with dilated cardiomyopathy than in healthy controls in terms of GLCM features, and the diagnostic accuracy using GLCM features was 0.85 ( 0.07). 32…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that homogeneity, energy, and correlation were higher in patients with dilated cardiomyopathy than in healthy controls in terms of GLCM features, and the diagnostic accuracy using GLCM features was 0.85 ( 0.07). 32…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, texture radiomic features allow the quantification of spatial inter-pixel relationships using more advanced matrix analysis methods (24,25). Through this, signal intensities patterns within the ROI may be numerically quantified using pre-agreed mathematical definitions.…”
Section: Texture-based Radiomics Featuresmentioning
confidence: 99%
“…al. [19] also shows that texture analysis of native T 1 maps can differentiate between DCM and control subjects. Similarly, Neisius, et.…”
Section: Introductionmentioning
confidence: 85%
“…For example, signal variation in cardiac MR images may contain additional information reflecting underlying pathophysiology [12][13][14] that is not being quantified. Radiomics [15] and texture image analysis have been recently applied to cardiac MR images [16][17][18][19][20] to extract new quantitative features that may provide diagnostic information. That is, radiomics quantitatively extract high-dimensional feature to differentiate images beyond mean signal value such as signal heterogeneity [17].…”
Section: Introductionmentioning
confidence: 99%